2018
DOI: 10.1093/hmg/ddy140
|View full text |Cite
|
Sign up to set email alerts
|

A plausibly causal functional lupus-associated risk variant in the STAT1–STAT4 locus

Abstract: Systemic Lupus Erythematosus (SLE or lupus) (OMIM: 152700) is a chronic autoimmune disease with debilitating inflammation that affects multiple organ systems. The STAT1-STAT4 locus is one of the first and most highly-replicated genetic loci associated with lupus risk. We performed a fine-mapping study to identify plausible causal variants within the STAT1-STAT4 locus associated with increased lupus disease risk. Using complementary frequentist and Bayesian approaches in trans-ancestral Discovery and Replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…The gene encoding STAT1 is located adjacent to STAT4 , and studies of lymphoblastoid cell lines (LCLs) generated from B cells of SLE patients found increased mRNA levels of STAT1 in STAT4 risk allele carriers. This effect was possibly mediated by allele‐dependent binding of the transcription factor HMGA1 to rs11889341 located in the third intron of STAT4 54 . In contrast to these data, no association between STAT4 genotype and STAT1 protein levels was found in peripheral blood B cells from SLE patients, 51 or healthy donors (unpublished data from 96 healthy individuals, P = .35).…”
Section: Connecting Genetic Risk Variants To Cellular Functionsmentioning
confidence: 67%
“…The gene encoding STAT1 is located adjacent to STAT4 , and studies of lymphoblastoid cell lines (LCLs) generated from B cells of SLE patients found increased mRNA levels of STAT1 in STAT4 risk allele carriers. This effect was possibly mediated by allele‐dependent binding of the transcription factor HMGA1 to rs11889341 located in the third intron of STAT4 54 . In contrast to these data, no association between STAT4 genotype and STAT1 protein levels was found in peripheral blood B cells from SLE patients, 51 or healthy donors (unpublished data from 96 healthy individuals, P = .35).…”
Section: Connecting Genetic Risk Variants To Cellular Functionsmentioning
confidence: 67%
“…The STAT4 variant has previously been associated with a more severe disease phenotype including ischaemic stroke and increased SDI scores 17–21. Patients with SLE carrying this risk variant display an augmented IFN-γ production in T cells and elevated STAT1 expression in B cells 39 40. Because of the entailed potential therapeutic opportunity, we believe our confirmation of the association of this variant with organ damage is valuable.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, neither variant was shown with long range chromatin interactions in the in the currently available HI-C data via the 3D genome browser. Despite the lack of functional information from these publicly available databases, functional information is available via a 2018 study, where transancestral mapping identified rs11889341 with strong association with SLE ( 65 ). This study focused on the STAT1-STAT4 region and found rs11889341 was associated with STAT1 expression in B-cells through increased binding of the transcription factor, HMGA1 ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lack of functional information from these publicly available databases, functional information is available via a 2018 study, where transancestral mapping identified rs11889341 with strong association with SLE ( 65 ). This study focused on the STAT1-STAT4 region and found rs11889341 was associated with STAT1 expression in B-cells through increased binding of the transcription factor, HMGA1 ( 65 ). Given the relationship between transcription factor binding and DNA topology ( 20 , 31 , 32 , 66 , 67 ), we hypothesize that the identified functional activity of rs11889341 (via HMGA1 binding) may be mediated by the large MGW change imposed by the SNP’s alleles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation